Pengaruh Pendidikan Kewirausahaan, Pola Pikir Kewirausahaan, Dan Kreativitas Terhadap Intensi Berwirausaha Mahasiswa (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2020) - Dewi, Anisa Hasna; Wahono, Budi; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine the influence of entrepreneurship education, entrepreneurial mindset, and creativity on the entrepreneurial intentions of students at the Faculty of Economics and Business, Islamic University of Malang class of 2020. The research method used is Explanatory Research with a quantitative approach. The population of this study was 699 students from the class of 2020, Faculty of Economics and Business, Islamic University of Malang, with a sample of 87 respondents selected using the Purposive Sampling technique. The research results show that entrepreneurship education, entrepreneurial mindset, and creativity significantly influence students' entrepreneurial intentions. Entrepreneurship education makes a significant positive contribution to students' entrepreneurial intentions, which indicates that entrepreneurial knowledge and skills encourage individual interest in entrepreneurship. Keywords : Enterpreneurship Education, Entrepreneurial Mindset, Creativity, Entrepreneurial Intentions